Fuzzy Logic for Automatically Performance Assessment using CIOWA Model - Mufadhol Mufadhol; Siswanto Siswanto; Maya Utami Dewi (Journal of Telematics and Informatics, 2018)
STEKOM is an institution accommodating almost 500 employees, always evaluates their performance and giving awards to achievement every year’s completed. Fuzzy logic is very suitable to be used in performance appraisal because it can process complex and variatif  data, as well as uncertain to be valid data. One of the models in fuzzy logic is the Consistency Induced Ordered Weighted Averaging method system by reducing the operator Averaging Mean and assigning a consistency index value used to analyze fuzzy preference relationships, then using the results of the analysis in the preference aggregation process. This article will explain how to apply the Consistency Induced Ordered Weighted Averaging model in fuzzy logic to assess the performance of STEKOM employees by assigning weight to each attribute and variable, then from the weights and variables will be rated according to the value obtained so that the decision will be taken as a solution in giving awards and promotions to employees that can meet the principles of fairness, equality and approriateness.